Developing Elements of Agricultural Market As System and Aspects of Its Provision - Stepanenko, Serhiy; Bushnov, Valeriy (Pressing Problems of Public Administration, 2019)
The practice of the recent years testi es to the necessity for searching for new mechanisms and methods of state regulation of the economic development processes in the sphere of agricultura production. Analysis of the world and Ukrainian experience provides grounds for stating that a successfu modern economy requires state intervention and regulation. Without an active and ef cient state policy, it is impossible to ensure economic growth and sustainable economic development. The state regulation of the agricultural sector of the economy is intended to secure its balanced and stable development. The state regulation of the economy under the market conditions is a system of typical legislative executive and controlling measures which are used by authorized government institutions and non-governmental organizations with the aim to stabilize and adapt the existing socio-economic system to the current conditions. The paper objective is to consider and analyze the agricultural market as a system, and on this basis, to identify the most important legislative-legal aspects of creating its elements and ensuring its effective functioning. The concept used for obtaining optimal values of the agricultural market indices is directed to determine the primary and secondary objectives, principles, provisions and conditions for the market creation and functioning. High ef ciency of the agricultural market can be provided due to synthesis of institutional structures and selection of the values of their parameters, processes and algorithms that conform to the world level.